Multinationals, local capacity building and development the role of Chinese and European MNEs - Fu, Xiaolan (Cheltenham Edward Elgar Publishing, 2019)
Multinational enterprises (MNEs) are everywhere and the perception of their engagement in myriad activities ranges between extremely positive and extremely negative. Based on original comprehensive research, this groundbreaking book examines the impact of Chinese and European MNEs in the African context. Sharing knowledge and insights from the authors' empirical research, Multinationals, Local Capacity Building and Development uses Ghana as a case study to analyse trends in MNEs and assess the advantages and disadvantages of their involvement.
Includes bibliographical references and index.
Keywords: International business enterprises -- Development -- China; International business enterprises -- Development -- Europe; BUSINESS & ECONOMICS